A Career in Catalysis: Daniel Resasco - Joaquin Resasco; Jimmy Faria; Walter E. Alvarez; Steven Crossley; Gary L. Haller; Gary Jacobs; Johannes A. Lercher; Gengnan Li; Lance L. Lobban; Fábio B. Noronha; M. Pilar Ruiz; Tawan Sooknoi; et al. (ACS Catalysis, 2025)
Daniel Resasco is widely recognized for his significant contributions to the science and application of heterogeneous catalysis. In this Account, we highlight key points along his career path, demonstrating how fundamental insights─drawn from rigorous kinetic analysis, precise materials synthesis, and in situ characterization─enabled breakthroughs in areas ranging from strong metal–support interactions to biomass upgrading. Daniel’s work on selective ring opening of hydrocarbons influenced the production of cleaner diesel fuels, while his innovative methods for synthesizing single-walled carbon nanotubes accelerated progress in nanomaterial applications. He later pioneered the use of Pickering emulsions in catalysis, employing amphiphilic materials to control selectivity and facilitate product separation at water–oil interfaces. Throughout these varied application areas, Daniel consistently blended a rigorous mechanistic approach with pragmatic goals, ensuring that the concepts he uncovered could be translated across topics and have practical impact. Beyond his scientific contributions, we highlight Daniel’s commitment to supporting the next generation of researchers in catalysis science.
Keywords: Catalysis and Hydrodesulfurization Studies; Catalysis for Biomass Conversion; Zeolite Catalysis and Synthesis